Zinc Promotes Adipose-Derived Mesenchymal Stem Cell Proliferation and Differentiation towards a Neuronal Fate - Mi-Young Moon; Hyun Jung Kim; Bo Young Choi; Min Sohn; Tae Nyoung Chung; Sang Won Suh (Hindawi Limited, 2018)
Zinc is an essential element required for cell division, migration, and proliferation. Under zinc-deficient conditions, proliferation and differentiation of neural progenitors are significantly impaired. Adipose-derived mesenchymal stem cells (AD-MSCs) are multipotent stem cells that can differentiate into neurons. The aim of this study was to evaluate the effect of zinc on AD-MSC proliferation and differentiation. We initially examined the effect of zinc on stem cell proliferation at the undifferentiated stage. AD-MSCs showed high proliferation rates on day 6 in 30 μM and 100 μM of ZnCl2. Zinc chelation inhibited AD-MSC proliferation via downregulation of ERK1/2 activity. We then assessed whether zinc was involved in cell migration and neurite outgrowth during differentiation. After three days of neuronal differentiation, TUJ-1-positive cells were observed, implying that AD-MSCs had differentiated into early neuron or neuron-like cells. Neurite outgrowth was increased in the zinc-treated group, while the CaEDTA-treated group showed diminished, shrunken neurites. Furthermore, we showed that zinc promoted neurite outgrowth via the inactivation of RhoA and led to the induction of neuronal gene expression (MAP2 and nestin) in differentiated stem cells. Taken together, zinc promoted AD-MSC proliferation and affected neuronal differentiation, mainly by increasing neurite outgrowth.